2006
DOI: 10.1089/vim.2006.19.277
|View full text |Cite
|
Sign up to set email alerts
|

Study of IgG Subclass Profiles of Anti-HBs in Populations With Different HBV Infection Status

Abstract: To study IgG-specific subclasses of hepatitis B virus (HBV) surface antigen (anti-HBs), in different populations in Taiwan, a comparison was made between 104 chronic carriers (60 male and 44 female) and 439 recovered individuals (247 male and 192 female). Biochemical analyses of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were also performed. Among the 104 chronic carriers, 21 patients had abnormal ALT and AST levels (> 25 IU/ml). When comparing the patients with abnormal ALT and AST le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
3
8
2
Order By: Relevance
“…The IgG subclass pattern demonstrated in chronic carriers was consistent with the findings of Sä llberg et al [1990]. Moreover, the anti-HBe IgG2 level was the same as that demonstrated in earlier anti-HBc [Yang et al, 2001 and anti-HBs Tsai et al, 2006] studies by this group, and it was the lowest IgG isotype in chronic carriers and recovered individuals of both genders. The IgG subclass profiles of anti-HBe in chronic carriers did not change with liver inflammation (elevated ALT and AST) and were independent of sex and age, although the mean OD for the patients with elevated ALT and AST was higher.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The IgG subclass pattern demonstrated in chronic carriers was consistent with the findings of Sä llberg et al [1990]. Moreover, the anti-HBe IgG2 level was the same as that demonstrated in earlier anti-HBc [Yang et al, 2001 and anti-HBs Tsai et al, 2006] studies by this group, and it was the lowest IgG isotype in chronic carriers and recovered individuals of both genders. The IgG subclass profiles of anti-HBe in chronic carriers did not change with liver inflammation (elevated ALT and AST) and were independent of sex and age, although the mean OD for the patients with elevated ALT and AST was higher.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies suggested that IgG1 is the most predominant anti-HBs IgG subclass in chronic carrier, recovered, and vaccinated groups . Samples from both chronic carriers and vaccinees exhibited a significantly higher concentration of antiHBs total IgG and IgG1 than those from recovered patients [Tsai et al, 2006]. The results of previous studies also suggest that, for asymptomatic carriers, the predominant anti-HBc subclass is IgG1, while IgG3 titers are higher relative to IgG1 in patients with liver cirrhosis [Akbar et al, 1991;Yang et al, 2001Yang et al, , 2005.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, we believe that this also holds true for other gastroenteroviruses, since our previous studies and other research groups have shown that IgG1 and IgG3 are the main IgG subclasses found in infection by human cytomegalovirus [81], human herpes virus 6 [82], hantavirus [83,84], and human immunodeficiency virus [85], and hepatitis B virus [86][87][88][89]. The cross-regulation between Th1 and Th2 cytokines is associated with the development of antigen pathogenesis [64].…”
Section: Transmissions Of Gastroenteroviruses and Host Immune Responsesmentioning
confidence: 77%
“…In BALB/c mice, IgG1 was the predominant subclass response when the orally administered subunit vaccines were delivered with CT as an adjuvant (12). IgG1 has also been reported to be the predominant IgG subclass of anti-HBs (2,14,17).…”
mentioning
confidence: 99%